INDEKS HARGA YANG DITERIMA PETANI (IT), INDEKS HARGA YANG DIBAYAR PETANI (IB), DAN NILAI TUKAR PEMBUDIDAYA IKAN (NTPI) SERTA PERUBAHANNYA - Melati Sihombing (Journal of Innovation Research and Knowledge, 2026)
The Farmer Price Index (IT) and the Farmer Paid Price Index (IB) are essential indicators for describing farmers’ economic conditions, while the Fish Farmer Terms of Trade (NTPi) is used to evaluate the welfare level of fish farmers. IT reflects changes in prices received by farmers from agricultural production, whereas IB indicates changes in the prices of goods and services paid by farmers for household consumption and production costs. NTPi is calculated as the ratio between the price index received and the price index paid by fish farmers, making it an important measure of purchasing power and welfare. Variations in IT, IB, and NTPi are influenced by market price fluctuations, production costs, and macroeconomic conditions. An increase in IT that exceeds IB indicates an improvement in farmers’ welfare. Conversely, when IB increases more rapidly than IT, farmers’ welfare tends to decline. Therefore, analyzing IT, IB, and NTPi and their changes is crucial as a basis for evaluating government policies aimed at improving the welfare of farmers and fish cultivators.